European Union legislation regarding waste processing technology - Rymarchuk R.; Mykhaniv V. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the work is to analyze the legislation of the European Union in the field of waste prevention and management. Method. In the presentation of the material of the article, generally scientific, systematic and functional methods of research are applied. The environmental legislation of the European Union has been developed and improved over the last 30 years and today it includes about 300 legal acts, namely directives, regulations, decisions and recommendations. In addition to them, a large number of bulletins and other political documents related to the environmental legislation of the countries of the European Union are issued. However, the national legislation and administrative practice of the associated countries of Central and Eastern Europe have to be harmonized with the EU environmental legislation. Results. The growing consumption of goods leads to the accumulation of a mass of waste that cannot be quickly processed and has a harmful effect on the environment. The EU policy on waste management is aimed at reducing the impact of waste on the environment, health and increasing the efficiency of resource use in Europe. The long-term goal is to transform Europe into a recycling society, avoiding waste or using unavoidable waste as a resource whenever possible. The goal is to achieve much higher levels of waste recycling and minimize the extraction of additional natural resources. Correct waste management is a key element in ensuring resource efficiency and sustainable growth of the economies of European countries. Scientific novelty. As a result of the study, it was established that the disposal of waste leads to pollution of surface water, underground water, soil and air. Therefore, the legislation should contain a specific goal to reduce landfills. EU member states must make efforts so that, starting from 2030, all waste is suitable for recycling or another form of disposal, in particular, municipal waste will not be accepted for landfills, with the sole exception of those wastes whose storage provides the best environmental results. In addition, by 2035, EU member states must ensure that the amount of household waste in landfills is reduced to 10% of the total amount. Practical significance. The results of the research can be used in the implementation of the European Union legislation into national legislation in waste management.